Bovine and equine manure doses in the initial growth of white ipe seedlings - Vieira, Cristiane Ramos; Samara de Assis Carneiro, Rayza; Araujo Botelho, Rosangela; Paz da Costa, Patrícia (Revista Ecologia e Nutrição Florestal - ENFLO, 2022)
The application of organic residues can be a good alternative for the seedlings production, provided that, in an adequate amount for the species to be propagated. Therefore, experiments were developed to evaluate the initial growth of white ipe seedlings (Tabebuia rose-alba (Ridl.) Sandwith in different doses of bovine and equine manure. The experiments were carried out in a completely randomized design with five doses (treatments) and five repetitions for each type of manure, being: T0 - without addition of manure; T1 - 10 Mg ha-1; T2 - 20 Mg ha-1; T3 - 30 Mg ha-1; T4 - 40 Mg ha-1. At the end of 90 days, the morphological characteristics of the white ipe seedlings were evaluated. The addition of bovine and equine manure to the soil improved the conditions for the growth of white ipe seedlings, and the dose of 40 Mg ha-1 was the most favorable for the species, for both manure types.